Stakeholders' Views about the Management of Stable Chronic Conditions in Community Pharmacies - Mansour M. Alotaibi; Louise Hughes; Jenna L. Bowen; William R. Ford (MDPI AG, 2022)
The role of the community pharmacist has evolved to include the provision of more clinical services for patients. Those people who have stable chronic conditions will be managed in community pharmacies. This qualitative study used semi-structured in-depth interviews to understand the potential of providing additional patient-centred care for patients with stable chronic conditions in community pharmacies and identify potential limitations of this approach. Participants were recruited from Welsh Government, Local Health Boards (LHBS), Community Pharmacy Wales (CPW) and the Royal Pharmaceutical Society Wales (RPSW). The interviews were audio-recorded, transcribed verbatim, and analysed thematically. Eight interviews were conducted. The identified themes were as follows: (1) inconsistency and bureaucracy in commissioning pharmacy services; (2) availability of funding and resources; (3) disagreement and uncertainty about the contribution of the community pharmacy sector; (4) continuity of patient medical information and fragmented care; (5) accessibility, capacity and facilities in community pharmacy; (6) pharmacy education and clinical expertise, and (7) patient acceptability. It was clear that the potential benefit of managing stable chronic diseases in community pharmacies was recognised; however, several limitations expressed by stakeholders of pharmacy services need to be considered prior to moving forward.